Modern weapons and military equipment for issue 2-2015 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Azerbaijan developing ZKDM combat vehicle Fire works: ARS seek greater range and accuracy Iran shows updated Falaq-1 and Falaq-2 rockets TOS-1A advances Russian firepower Iran reveals its Bavar-373 SAM New gun shapes up for Russian MBT